Memória musical de São Carlos: retratos de um conservatório - Amato, Rita de Cássia Fucci (2004)
The aim of this thesis to establish considerations and understanding on the historical and cultural meaning of the Conservatório Musical de São Carlos , founded in 1947. The institution is pictured with the intention of unveiling its significance from its golden age´ to its decline, culminating in its closure in 1991. Research was carried out based on documental papers (primary sources) belonging to the Biblioteca Municipal de São Carlos (Municipal Library of São Carlos) and also on interviews of former teachers and students, with the aim of mapping its 44 years of existence. An analysis of the content of the different interviews made it possible to clarify the formation of the student body their families, their socioeconomic and cultural situation, thus establishing the real profile of the target audience of the institution, - their intentions, longings and professional perspectives. It also discloses the possible reasons for the success and long existence of the conservatorium its pedagogic strength and the musical legacy passed on from generation to generation of students.